2021
DOI: 10.1186/s13634-021-00778-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence mechanism of running sportswear fatigue based on BP neural network

Abstract: The fatigue of running sportswear is reflected in the fatigue caused by the tightness of the tights on the skin surface of the limbs, trunk, and other parts during long-term running sports. However, the current research on the fatigue of running sportswear is not deep enough. Therefore, the purpose of this study is to study the mechanism of the fatigue of running sportswear based on BP neural network. This article first takes sportswear as the starting point and uses the surface myoelectricity index as a physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In this study, during the progressive cycling exercise, we observed (in all groups) a shift towards lower EMG frequencies (i.e., a low-frequency fatigue) together with an increased AEMG. This relationship is considered to be an indicator of NMF [ 50 ]. Other studies have confirmed this mechanism, based on a higher AEMG signal toward the end of the exercise [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, during the progressive cycling exercise, we observed (in all groups) a shift towards lower EMG frequencies (i.e., a low-frequency fatigue) together with an increased AEMG. This relationship is considered to be an indicator of NMF [ 50 ]. Other studies have confirmed this mechanism, based on a higher AEMG signal toward the end of the exercise [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the precision is achieved, the algorithm ends. Otherwise, a new learning sample and the expected output are selected and transferred to a step to enter the next round of learning [27]. ere are various parameters of the BPNN algorithm, which are explained as follows:…”
Section: Bp Neuralmentioning
confidence: 99%
“…Muscle strength declines progressively during exercise, so fatigue occurs before the task failure ( Gandevia, 2001 ). There are many examples of application fields involving muscle fatigue, including sports ( Simsek, 2017 ; Kuniszyk-Jozkowiak et al, 2018 ; Liu et al, 2019 ; Hedayatpour et al, 2021 ; Liu and Li, 2021 ; Rodriguez-Rosell et al, 2021 ), rehabilitation ( Gaudet et al, 2018 ; Kim et al, 2018 ; Meng et al, 2019 ; Na et al, 2020 ; Fundaro et al, 2021 ; Sato et al, 2021 ), and occupation ( Alberto et al, 2018 ; Fang et al, 2021 ; Ji and Huang, 2021 ; Yu et al, 2021 ; Gonzalez-Zamora et al, 2022 ). Physiological signals, biochemical assessments, and questionnaires are used to monitor exercise fatigue ( Halson and Shona, 2014 ).…”
Section: Introductionmentioning
confidence: 99%